A Novel Approach to Similarity Based Link Prediction Based on the Hyrbid of Jaccard and AA Indices for Complex Networks Including Social Media as well as Food Science (International Journal of Food and Nutritional Sciences, 2022)
Predicting missing or future connections within complex networks is crucial across diverse domains, including social media and food science. This paper proposes a novel hybrid approach for similarity-based link prediction by integrating the Jaccard coefficient and the Adamic-Adar (AA) index. This integrated approach demonstrates superior performance in both social media and food science networks compared to traditional and modern methods. The Jaccard coefficient, a well-established measure, quantifies node similarity based solely on the number of shared neighbors. While effective, it neglects the significance of individual neighbors in influencing potential links. The AA index compensates for this by assigning higher weights to shared neighbors with lower degrees, emphasizing the role of rare or less connected nodes as potential drivers of interaction. Our hybrid approach leverages the complementary strengths of both measures. By combining Jaccard's focus on shared neighbor count with AA's emphasis on neighbor importance, we capture a multifaceted perspective on node similarity. This comprehensive approach outperforms traditional Jaccard-based methods and modern techniques utilizing complex feature sets. We demonstrate the hybrid method's efficacy on real-world social media and food science networks, consistently achieving superior performance in terms of established link prediction metrics like AUC (Area Under Curve) and Precision-Recall. The improved accuracy stems from the hybrid approach's ability to discern subtle link formation patterns that traditional and modern methods might overlook. This sensitivity is particularly valuable in social media networks, where fleeting interactions and nuanced connections are commonplace, and in food science networks, where intricate interactions between ingredients, processes, and outcomes can be crucial. This novel hybrid technique offers a valuable tool for link prediction in both social media and food science networks. It facilitates improved understanding of social dynamics, user behavior, food systems, and product development. The approach's potential extends beyond these specific domains, offering a practical and efficient solution for link prediction in diverse complex networks across various research and application areas.